Uso da modelagem molecular na solução de problemas em química - Madureira, Lucas Sousa (Universidade Federal de São Carlos, 2014)
The studies presented herein show the use of molecular modelling coupled to spectroscopic data to tackle four different problems in organic chemistry. In the first study, the sulfonylation of the primary hydroxyl group of the compound (2R,3S,6S)-2-(hydroxymethyl)-6-(1-phenyl-1H-1,2,3-triazol-4-yl)-3,6-dihydro-2Hpyran- 3-ol was addressed. The results show that the occurrence of the reaction depends on the stability of the S Cl secondary interactions and of the C-H Cl hydrogen bonds along the reaction pathway. The second investigation was the cycloaddition between benzyl azide and (organotelanil) alkynes. This reaction has a high driving force towards the products and generates fast and selectively a triazole with a n-butyltelluride substituent attached at position 5, which is stabilized by CH...Te interactions. So this cycloaddition fits the requirements of Click Chemistry. In third place, the conformations and relative configurations of 7 and 9 membered rings were elucidated by evaluating steric strain. The 7 membered ring shows a twisted chair conformation (TC) with C1, C7 and C10 having relative configurations S, R and S. The 9 membered ring has a twisted chair-chair conformation (TCC) and relative configurations R, S of C7 and C10. The fourth study was the optimization of rotational conformations of 1- (arylsulfonyl)indole derivatives. The different optimized conformations have the same stability and low rotational energy barrier, so that in the solid state the number of independent molecules in the asymmetric unit essentially depends on the packing intermolecular interactions. Regarding the stability of sulfonamide bonds the importance of hyperconjugative effects were showed, and the origin of the rotational barrier in the S-N bond is explained by the difference in steric hindrance and electrostatic interactions in the transition and the fundamental states.
The use of molecular modelling in solving problems in chemistry
Keywords: Físico-química; Modelagem molecular; Sulfonamidas; Sulfonilação; Anéis médios; Click chemistry; CIENCIAS EXATAS E DA TERRA::QUIMICA